2014
DOI: 10.1017/s1751731114000871
|View full text |Cite
|
Sign up to set email alerts
|

Using classification trees to detect induced sow lameness with a transient model

Abstract: Feet and legs issues are some of the main causes for sow removal in the US swine industry. More timely lameness detection among breeding herd females will allow better treatment decisions and outcomes. Producers will be able to treat lame females before the problem becomes too severe and cull females while they still have salvage value. The objective of this study was to compare the predictive abilities and accuracies of weight distribution and gait measures relative to each other and to a visual lameness dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Further research working with animals with an identified lameness problem beforehand or longitudinal studies need to be undertaken to correlate a measure from automated methods to a type of lameness and to determine its threshold value for an accurate diagnosis. This type of longitudinal research has been undertaken in induced-lame sows (Abell et al, 2014) and needs to be developed on sows with naturally occurring lameness to reflect the variety of lameness problems. Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…Further research working with animals with an identified lameness problem beforehand or longitudinal studies need to be undertaken to correlate a measure from automated methods to a type of lameness and to determine its threshold value for an accurate diagnosis. This type of longitudinal research has been undertaken in induced-lame sows (Abell et al, 2014) and needs to be developed on sows with naturally occurring lameness to reflect the variety of lameness problems. Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…Records were excluded from the data set based on the following criteria: 1 (2) if individually both front legs or both rear legs of the sow weighed less than 4.5 kg; or (3) if any foot individually weighed less than 0 kg. These criteria were previously used by Abell et al (2014) to indicate that the sow's feet were not properly positioned on each quadrant of the force plate. When the feet are not positioned correctly, the measurements recorded are not an accurate representation of the sow's weight distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The P95 provides a more robust value for the maximum force applied by the sow, since extreme values occurred when the sow pushed up on the feed trough or adjusted her weight. These values were also used by Abell et al (2014) to develop a lameness classification tree from sows' force distributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abell and others compared of the predictive abilities and accuracies of weight distribution and gait measures relative to one another and to visual lameness methods on induced sow lameness. They found that weight distribution measurements had a higher predictive ability than the gait measurements (Abell et al 2014). Lastly, a study by Bertholle and colleagues investigated the use of radiographs, a visual lameness scoring scheme and a quantitative pressure-mat bases locomotion analysis system.…”
Section: Detection and Evaluation Methodsmentioning
confidence: 99%